1997
DOI: 10.1007/bf02910665
|View full text |Cite
|
Sign up to set email alerts
|

Bioavailability of selenium from veal, chicken, beef, pork, lamb, flounder, tuna, selenomethionine, and sodium selenite assessed in selenium-deficient rats

Abstract: The bioavailability of selenium (Se) from veal, chicken, beef, pork, lamb, flounder, tuna, selenomethionine (SeMet), and sodium selenite was assessed in Se-deficient Fischer-344 rats. Se as veal, chicken, beef, pork, lamb, flounder, tuna, SeMet, and sodium selenite was added to torula yeast (TY) basal diets to comprise Se-inadequate (0.05 mg Se/kg) diets. Se as sodium selenite was added to a TY basal diet to comprise a Se-adequate (0.10 mg Se/kg), Se-control diet. The experimental diets were fed to weanling Fi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
1
2

Year Published

1998
1998
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(17 citation statements)
references
References 22 publications
1
13
1
2
Order By: Relevance
“…Selenium bioavailability has classically been determined by measuring the repletion of tissue selenium concentrations and GSHPx activities in Se-deficient rats (Wen et al, 1997). It has been repeatedly demonstrated that there is a good correlation between selenium tissue accumulation, enzyme activity and selenium status in situations of deficient or marginal selenium supply, whereas the correlation clearly weakens with nutritionally adequate selenium intake (Wolfram, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…Selenium bioavailability has classically been determined by measuring the repletion of tissue selenium concentrations and GSHPx activities in Se-deficient rats (Wen et al, 1997). It has been repeatedly demonstrated that there is a good correlation between selenium tissue accumulation, enzyme activity and selenium status in situations of deficient or marginal selenium supply, whereas the correlation clearly weakens with nutritionally adequate selenium intake (Wolfram, 1999).…”
Section: Discussionmentioning
confidence: 99%
“…101 The bioavailability of Se from veal has been reported to be similar to beef, but the bioavailability of Se from lamb was reported to be lower than beef. 102 Concentrations of Se in beef reflect the amount of Se in the plants grazed; consequently beef produced in high-Se areas may have Se concentrations many-fold higher than the beef of animals produced in low-Se areas. 103 Seleniumenhanced beef also can be produced in a feedlot by feeding animals high-Se feedstuffs.…”
Section: Selenium In Meat and Animal Productsmentioning
confidence: 99%
“…The intake of selenium-rich fish has been shown to be highly correlated with glutathione peroxidase activity and selenium protein-P plasma levels (Bergmann et al, 1998;Hagmar et al, 1998). There are reports that selenium availability from tuna fish and other seafood is low (Robinson & Thomson, 1983;Mutanen, 1986;Meltzer et al, 1993;Wen et al, 1997); however, there are few studies investigating the absorption of selenium from fish in humans, and experiments using rats as models have reported lower absorption from fish muscle compared with meat and offal (Thomson et al, 1975;Richold et al, 1977). It has also been suggested that selenium from animal sources is less available than selenium derived from plant sources (Young et al, 1982).…”
Section: Introductionmentioning
confidence: 99%